Physical barriers faced by People with Disabilities (PwDs) in shopping mall - Bashiti, Alaa; Abdul Rahim, Asiah (Elsevier Ltd., 2016)
This paper intends to discuss the issue of accessibility, connectivity and usability in the facilities that used by people with disabilities (PwDs) in shopping malls and the significance of the latest Malaysian standards (MS 1184:2014) Universal Design and Accessibility in the Built Environment-Code of Practice in evaluating shopping malls. Three case studies have been selected in Malaysia to evaluate accessibility for PwDs. Both qualitative and quantitative methods are applied in this study, Data were collected using semi structured interviews with PwDs to find out their perception on the level of accessibility of these buildings. Access audit and site observation were also carried out.